A survey exploring self-reported indoor and outdoor footwear habits, foot problems and fall status in people with stroke and Parkinson's. Issue 1 (December 2016) - Bowen, Catherine; Ashburn, Ann; Cole, Mark; Donovan-Hall, Margaret; Burnett, Malcolm; Robison, Judy; Mamode, Louis; Pickering, Ruth; Bader, Dan; Kunkel, Dorit
Abstract Background Ill-fitting shoes have been implicated as a risk factor for falls but research to date has focused on people with arthritis, diabetes and the general older population; little is known about people with neurological conditions. This survey for people with stroke and Parkinson's explored people's choice of indoor and outdoor footwear, foot problems and fall history. Methods Following ethical approval, 1000 anonymous postal questionnaires were distributed to health professionals, leads of Parkinson's UK groups and stroke clubs in the wider Southampton area, UK. These collaborators handed out survey packs to people with a confirmed diagnosis of stroke or Parkinson's. Results Three hundred and sixty three completed surveys were returned (218 from people with Parkinson's and 145 from people with stroke). Most respondents wore slippers indoors and walking shoes outdoors and considered comfort and fit the most important factors when buying footwear. Foot problems were reported by 43 % (95 % confidence intervals 36 to 52 %; stroke) and 53 % (95 % confidence interval 46 to 59 %; Parkinson's) of respondents; over 50 % had never accessed foot care support. Fifty percent of all respondents reported falls. In comparison to non-fallers, a greater proportion of fallers reported foot problems (57 %), with greater proportions reporting problems impacting on balance and influencing choice of footwear (p  < 0.01) in comparison to non-fallers in each case. Forty-seven percent of fallers with foot problems had not accessed foot care support. Conclusions Many people with stroke and Parkinson's wear slippers indoors. A high percentage of these individuals reported both foot problems and falls impacting on footwear habits and choice of footwear; however many did not receive foot care support. These findings highlight that further exploration of footwear and foot problems in these populations is warranted to provide evidence based advice on safe and appropriate footwear to support rehabilitation and fall prevention.